2006
DOI: 10.1097/01.ta.0000205862.57701.48
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Distress Syndrome Secondary to Inhalation of Chlorine Gas in Sheep

Abstract: Cl2 causes severe, dose-related lung injury, with features seen in both smoke inhalation and in ARDS secondary to systemic disease. This model will be used to test new therapeutic modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…In our first series of experiments, we exposed mice to Cl 2 at concentrations likely to be encountered in industrial accidents or deliberate release of Cl 2 into the atmosphere (19,26,27) and measured Na ϩ -dependent AFC in vivo at various times post exposure after the mice were returned to room air. Because our results indicated that exposure to Cl 2 decreased AFC, we performed additional studies in Xenopus oocytes injected with cRNAs of the human ENaC (hENaC) subunits (␣-, ␤-, and ␥-ENaC) to identify the cellular and molecular mechanisms by which HOCl (formed by the hydrolysis of Cl 2 gas) as well as reactive intermediates formed by the reaction of HOCl with components of the media decreased Na ϩ -and amiloride-sensitive currents (I Na and I amil , respectively).…”
mentioning
confidence: 99%
“…In our first series of experiments, we exposed mice to Cl 2 at concentrations likely to be encountered in industrial accidents or deliberate release of Cl 2 into the atmosphere (19,26,27) and measured Na ϩ -dependent AFC in vivo at various times post exposure after the mice were returned to room air. Because our results indicated that exposure to Cl 2 decreased AFC, we performed additional studies in Xenopus oocytes injected with cRNAs of the human ENaC (hENaC) subunits (␣-, ␤-, and ␥-ENaC) to identify the cellular and molecular mechanisms by which HOCl (formed by the hydrolysis of Cl 2 gas) as well as reactive intermediates formed by the reaction of HOCl with components of the media decreased Na ϩ -and amiloride-sensitive currents (I Na and I amil , respectively).…”
mentioning
confidence: 99%
“…3,9,12 There have been previous studies carried out with various doses and duration on chlorine gas in rats, sheep, porcine and dormice. 4,[13][14][15] We selected rats as the experiment animals in our study, since they met our conditions the best. Most of the recently reported chlorine gas exposures include exposures caused by the inhalation of toxic vapor arising from mixing of hypochlorite-containing household cleaning products with acid products.…”
Section: Resultsmentioning
confidence: 99%
“…15 During the follow-up, no deaths were seen in the Group treated with 120 ppm chlorine gas, while five out of 11 sheep had died in the group treated with 240-350 ppm, and 10 out of 12 sheep died in the group treated with 400-500 ppm chlorine gas. In the microscopic examination of the pulmonary tissues of the group treated with 120 ppm chlorine gas, they found localized regional necrosis associated with capillary congestion, edema, fibrin deposits and acute inflammation in the bronchial epithelium.…”
Section: Figurementioning
confidence: 99%
“…Based on the results of Yamamoto et al (17) and other previous reports (18)(19)(20), it has been suggested that there may be a latent period lasting up to 10 h and that symptoms may worsen 48 h following exposure to chlorine gas. In the current study, the patient developed respiratory failure after 4 h and symptoms worsened 13-14 h following initial exposure.…”
Section: Discussionmentioning
confidence: 99%